Empowerment, Emotional Intelligence, and Innovation's Impact on Organizational Citizenship Behavior Among BPJS Health Employees - KRMT Roy Suryo Notodiprojo; Hamidah Hamidah; Ari Saptono (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study's problem is related to organizational citizenship behavior in BPJS Health personnel. The purpose of this study is to investigate the direct and indirect effects of empowerment, emotional intelligence, and innovation on organizational citizenship behavior. The structural equation modeling (SEM) method is used in this study, together with the SmartPLS application. This study had 197 BPJS Health personnel as participants. According to the findings of this study, innovation has the highest and most substantial influence on corporate citizenship behavior. Empowerment and emotional intelligence are also important factors in organizational citizenship behavior.